The Effect of Position Specifications, Tenure, and Job Placement on Work Productivity in District Government X - Jatiarso, Windu; Hakim, Azis (CV. Publikasi Indonesia, 2025)
There are several things that are considered to have an influence on work productivity in the district government, including job specifications, work period and job placement. However, this has not been explained in more depth. Therefore, researchers are encouraged to conduct research on the influence of job specifications, work period, and job placement on work productivity in the X district government. The purpose of this study is to determine whether or not there is an influence of job specifications, work period, and job placement on work productivity in the X district government. The research method used is qualitative with data collection techniques through observation, interviews and documentation, where interviews were conducted with 10 employees in the X district government. The research data that has been collected will be analyzed in depth to determine the results of the study. The results of the study indicate that clear job specifications, work period and appropriate job placement according to employee abilities can increase employee work productivity in the X district government positively and significantly. With this, the government should carry out clear job specifications considering the work period and employee abilities in carrying out work placement so that work productivity increases and organizational goals can be achieved effectively and efficiently.